2008
DOI: 10.1007/s00442-008-1226-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exotic parasitoids on populations of a native Hawaiian moth assessed using life table studies

Abstract: The impact of alien species on native organisms is a cause for concern worldwide, with biological invasions commonplace today. Suppression efforts targeting many invasive species have included introductions of biological control agents. The numerous releases of biological control agents in the Hawaiian archipelago have resulted in considerable concern for non-target impacts, due to high levels of non-target parasitism observed to occur in some cases. This study investigated the impact of introduced Hymenoptera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 36 publications
(43 reference statements)
1
32
0
Order By: Relevance
“…No new larval parasitoid species were recorded during these studies besides the ones already reported in previous studies (Kaufman and Wright 2009b;Kaufman et al 2008), even though sampling was conducted over a larger area than the previous studies. This suggests that the sampling effort was adequate to include all species of parasitoids attacking U. stellata.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…No new larval parasitoid species were recorded during these studies besides the ones already reported in previous studies (Kaufman and Wright 2009b;Kaufman et al 2008), even though sampling was conducted over a larger area than the previous studies. This suggests that the sampling effort was adequate to include all species of parasitoids attacking U. stellata.…”
Section: Resultsmentioning
confidence: 83%
“…The observed differences among study sites may be the result of differences in ecological factors such as elevation, level of disturbance by alien plants, host plant density, density of insect host, and canopy cover. Results presented in previous studies have shown that adventive parasitoids, rather than purposely introduced ones, were responsible for the greater part of U. stellata mortality (Kaufman and Wright 2009b;Kaufman and Wright 2010). At low and low-medium elevations (between 240 and 900 m asl), the parasitoid assemblage was dominated by adventive species.…”
Section: Introductionmentioning
confidence: 90%
“…KAUFMAN & WRIGHT 2009). The relative role of predation in larval lepidopteran life tables is, however, often difficult to ascertain due to the difficulty of monitoring mobile life stages in the field and the uncertainty posed by the complete disappearance of larvae which may have variously either fallen from the plant, wandered away, or been removed by a predator.…”
Section: Discussionmentioning
confidence: 99%
“…This study based on food web analysis strongly suggested that the many introductions of biological control agents had detrimental effects but more recently, evidence is provided from more detailed studies that introduced biological control agents do not severely harm the native fauna. For instance, Kaufman and Wright (2009) studied the impact of introduced hymenopteran parasitoids on the endemic Hawaiian moth Udea stellata (Butler) (Lepidoptera: Crambidae) using detailed life-table studies. They found that parasitism accounted for 4.9% of the mortality observed compared with disappearance (predation) which accounted for 42.1% and unknown causes (16.5%).…”
Section: Environmentmentioning
confidence: 99%